Hepatitis B, hepatitis C, and mortality among HIV-positive individuals. (28th November 2017) - Thornton, Alicia C.; Jose, Sophie; Bhagani, Sanjay; Chadwick, David; Dunn, David; Gilson, Richard; Main, Janice; Nelson, Mark; Rodger, Alison; Taylor, Chris; Youssef, Elaney; Leen, Clifford; et al.
Abstract : Objectives: To compare rates of all-cause, liver-related, and AIDS-related mortality among individuals who are HIV-monoinfected with those coinfected with HIV and hepatitis B (HBV) and/or hepatitis C (HCV) viruses. Design: An ongoing observational cohort study collating routinely collected clinical data on HIV-positive individuals attending for care at HIV treatment centres throughout the United Kingdom. Methods: Individuals were included if they had been seen for care from 2004 onwards and had tested for HBV and HCV. Crude mortality rates (all cause, liver related, and AIDS related) were calculated among HIV-monoinfected individuals and those coinfected with HIV, HBV, and/or HCV. Poisson regression was used to adjust for confounding factors, identify independent predictors of mortality, and estimate the impact of hepatitis coinfection on mortality in this cohort. Results: Among 25 486 HIV-positive individuals, with a median follow-up 4.5 years, HBV coinfection was significantly associated with increased all-cause and liver-related mortality in multivariable analyses: adjusted rate ratios (ARR) [95% confidence intervals (95% CI)] were 1.60 (1.28–2.00) and 10.42 (5.78–18.80), respectively. HCV coinfection was significantly associated with increased all-cause (ARR 1.43, 95% CI 1.15–1.76) and liver-related mortality (ARR 6.20, 95% CI 3.31–11.60). Neither HBV nor HCV coinfection were associated with increased AIDS-related mortality: ARRs (95% CI) 1.07 (0.63–1.83) and 0.40 (0.20–0.81), respectively. Conclusion: The increased rate of all-cause and liver-related mortality among hepatitis-coinfected individuals in this HIV-positive cohort highlights the need for primary prevention and access to effective hepatitis treatment for HIV-positive individuals.